Sie sind auf Seite 1von 1

( a n ) ( b n ) c 2 n − 1 := a

(a n ) (b n ) c 2n1 := a n c 2n := b n (c n ) (a n ) (b n )

(a n ) (b n ) b n = 0 n N

(a)

(b)

n (a n b n ) = 0

lim

lim

n→∞

n

n

a

b = 1

lim

n→∞

a

n

b

n

= 1

lim

n (a n b n ) = 0

(a) (b)

(x n ) R

lim inf n x n lim sup n x n

lim sup n x n lim inf n x n

lim inf n x n < lim sup n x n

lim sup n x n = x R n N x n > x

k=1

k=1

k=1

( a 1) k

k

(1) k k 3

(k 2 + 1) 4/3

k!

k

k

a R a > 0

k=1

k + 4 k 2 3k + 7

k=1

k=0

(1) k ( k + 1 k)

k 4

3

k